The Formation of Children’s Religiosity: Integrating Manual-Digital Learning at Al-Azhar Cairo Islamic Elementary School, Banda Aceh - Mesi Rawanita; Silahuddin Silahuddin; Safrina Ariani (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The rapid development of information and communication technology (ICT) in the 21st century has significantly transformed the landscape of Islamic education. Objective: This study explores the process of forming children’s religiosity through a combination of manual and digital learning (blended learning) at Al-Azhar Cairo Islamic Elementary School, Banda Aceh. Method: Employing a qualitative descriptive approach, this research investigates how blended learning serves as a pedagogical model to harmonize digital flexibility with spiritual depth. Data were collected through interviews, observations, and documentation from teachers and students actively engaged in religious instruction. Results: The study finds that integrating manual learning—which emphasizes direct interaction, modeling, and moral habituation—with digital media such as Qur’an learning applications, interactive videos, and online platforms, fosters a balanced development of students’ cognitive, affective, and psychomotor religious dimensions. Teachers play multidimensional roles as murobbi (spiritual educator), mu’allim (knowledge transmitter), murshid (spiritual guide), and uswah hasanah (moral exemplar). Conclusion: The study concludes that digital learning, when positioned as enrichment rather than substitution, can strengthen children’s religiosity and promote an adaptive Islamic education model aligned with the digital era while preserving spiritual authenticity